A new coupling mechanism between two graphene electron waveguides for ultrafast switching. (15th February 2018) - Huang, Wei; Liang, Shi-Jun; Kyoseva, Elica; Ang, Lay Kee
Abstract: In this paper, we report a novel coupling between two graphene electron waveguides, in analogy the optical waveguides. The design is based on the coherent quantum mechanical tunneling of Rabi oscillation between the two graphene electron waveguides. Based on this coupling mechanism, we propose that it can be used as an ultrafast electronic switching device. Based on a modified coupled mode theory, we construct a theoretical model to analyze the device characteristics, and predict that the switching speed is faster than 1 ps and the on–off ratio exceeds 10 6 . Due to the long mean free path of electrons in graphene at room temperature, the proposed design avoids the limitation of low temperature operation required in the traditional design by using semiconductor quantum-well structure. The layout of our design is similar to that of a standard complementary metal-oxide-semiconductor transistor that should be readily fabricated with current state-of-art nanotechnology.